Design and performance validation on a solar louver with concentrating-photovoltaic-thermal modules. (May 2022) - Liang, Shen; Zheng, Hongfei; Wang, Xuanlin; Ma, Xinglong; Zhao, Zhiyong
Abstract: Traditional building integrated photovoltaic (BIPV) windows face the problems of low efficiency and unsatisfactory daylighting. Given this, this paper proposes a solar louver to harvest solar energy in the vertical building space for on-site electricity and heat generation. The solar louver is composed of concentrating photovoltaic-thermal (CPV-T) modules and allows users to adjust interior daylight according to individual demand. The design scheme of the CPV-T module and the solar louver is introduced. The CPV-T module's optical characteristics are revealed by optical simulations. The results illustrate that the CPV-T module can concentrate sunlight at the incident angle between 5° and 75° and holds the maximum concentration ratio of 3.14. Moreover, its concentration ratio can exceed 2.5 over the range of light incident angles between 15° and 45°. A prototype of the solar louver is manufactured and experimentally studied under actual weather conditions to illustrate its electricity and thermal collection performance. The results show that within the light incident angle of 20°–50°, the solar louver can maintain electrical efficiency above 4.18% and thermal collection efficiency above 55.6%. Additionally, the effective working hour is greater than 6 h, which provides a possibility to be used on buildings. Highlights: A solar louver composed of concentrating photovoltaic-thermal modules is proposed. The louver's concentration ratio can exceed 2.5 in light incident angle of 15°–45°. The louver allows user to adjust daylighting without reducing solar energy capture. Its effectiveness is demonstrated by experiment with energy efficiency over 59.7%.